2006
DOI: 10.1677/erc.1.01033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of gonadotropin-releasing hormone (GnRH)-I and -II-induced cell growth inhibition in ovarian cancer cells: role of the GnRH-I receptor and protein kinase C pathway

Abstract: In our previous studies, we demonstrated that ERK1/2 (extracellular signal-regulated protein kinase) and p38 MAPK (mitogen-activated protein kinase) are required for gonadotropin-releasing hormone (GnRH)-II-induced anti-proliferation of ovarian cancer cells. In the present study, we examined the role of the GnRH-I receptor, as well as the activation of protein kinase C (PKC), in the antiproliferative effect induced by GnRH-I or II in ovarian cancer cells. Our results demonstrated that Antide, a GnRH-I antagoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 41 publications
7
39
0
2
Order By: Relevance
“…In addition, cotreatment of cells with the GnRH antagonist antide, which is known to inhibit the functional activity of GnRH receptor (Li et al, 1994) and its downstream signaling (Kim et al, 2006), also prevented the upregulation of P-cadherin (Figure 1d), confirming a direct involvement of GnRH receptor in regulating P-cadherin expression. The increase in P-cadherin was not the result of changes in mRNA stability, as GnRHa did not affect the turnover rate of the P-cadherin mRNA (Figure 2a).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In addition, cotreatment of cells with the GnRH antagonist antide, which is known to inhibit the functional activity of GnRH receptor (Li et al, 1994) and its downstream signaling (Kim et al, 2006), also prevented the upregulation of P-cadherin (Figure 1d), confirming a direct involvement of GnRH receptor in regulating P-cadherin expression. The increase in P-cadherin was not the result of changes in mRNA stability, as GnRHa did not affect the turnover rate of the P-cadherin mRNA (Figure 2a).…”
Section: Resultsmentioning
confidence: 66%
“…inhibiting the GnRH receptor in the absence of GnRHa in these cells (Kang et al, 2000;Cheung et al, 2006;Kim et al, 2006), an autocrine system might exist in vivo. It is known that the GnRH precursor must be cleaved to become active (Cheng and Leung, 2005), and the lack of response with GnRH receptor inhibition in Figure 7 Cytoplasmic localization of p120 ctn is important for GnRH-mediated cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (2006) have recently shown that gonadotrophins follicle-stimulating hormone and luteinizing hormone (FSH and LH) are able to reduce the levels of GnRH II but not GnRH I mRNA in ovarian surface epithelium and cancer cell lines. Gonadotrophin treatment also reduced the expression of the type I GnRHIR in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of each may stabilise different receptor active conformations and allow ligand-specific selective signalling. Silencing of GnRHIR in ovarian cancer cells has certainly been shown to reverse the antiproliferative effects of GnRH II (Kim et al 2006). In contrast, Grundker et al (2004) working in ovarian and endometrial cells have reported that the GnRHIR is not required for the inhibitory effects of GnRH II.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, w1000 GnRH analogues have been identified and widely studied (Conn & Crowley 1994, Cheung et al 2006. Besides its well-known endocrine function, GnRH may directly regulate some extrapituitary reproductive tissues such as endometrium, ovary and placenta (Islami et al 2001, Chou et al 2003, Grundker et al 2004, Kim et al 2006. Recent studies revealed that both GnRH and GnRH receptors are expressed in the human endometrium and endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%